Synthesis and Application of Gold Nanoparticles in SPR Biosensors and Electrochemical Biosensors - Wu, Zian (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Gold nanoparticles (AuNPs) have garnered high attention in the field of nanotechnology owing to their distinctive optical, electronic, and chemical properties. Therefore, AuNPs are particularly valuable in the development of advanced sensor technologies. It is well known that the size and structure of gold nanoparticles are significantly affected by the synthesis methods. Therefore, studying the preparation methods of AuNPs is of great significance for achieving controllable performance. This would promote the application of AuNPs in biosensor. This paper discusses the synthesis methods of AuNPs, including the Turkevich, Brust-Schiffrin, seeding growth, and green synthesis techniques. In addition, the affection of the synthesis method on the morphology and functional properties of AuNPs are analyzed critically. The paper also explores the applications of AuNPs in biosensors, especially in surface plasmon resonance (SPR) biosensors and electrochemical biosensors. The modification of the sensors by AuNPs is proved to significantly enhance the sensitivity and specificity. This work contributes to achieve accurate and efficient detection of biological molecules.